2017
DOI: 10.2741/4526
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Enolase i ENO1 i a potential target in novel immunotherapies

Abstract: Alpha-enolase () is a metabolic enzyme involved in the synthesis of pyruvate. It also acts as a plasminogen receptor and mediates the activation of plasmin and extracellular matrix degradation. In tumor cells, is up-regulated and supports the Warburg effect; it is expressed at the cell surface, where it promotes cancer invasion, and is subjected to a specific array of post-translational modifications, namely acetylation, methylation and phosphorylation. overexpression and post-translational modifications could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…Moreover, AMPK is essential for the transient activation of Akt under hypoxia (Supplementary Fig. 7 C). Interestingly, ENO1 expression was induced by hypoxia in a more delayed manner that gradually increased until 12 h (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AMPK is essential for the transient activation of Akt under hypoxia (Supplementary Fig. 7 C). Interestingly, ENO1 expression was induced by hypoxia in a more delayed manner that gradually increased until 12 h (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…α-enolase (ENO1) is ubiquitous and has been detected in most tissues, whereas γ-enolase (ENO2) is expressed predominantly in nervous tissues and β-enolase (ENO3) mainly in skeletal muscle tissues 6 . Accumulating evidence has demonstrated that ENO1 is a multi-functional protein depending on its cellular localization 7 , 8 . Although the majority of ENO1 is cytosolic and promotes tumor pathogenesis and progression, ENO1 is also present on the cell surface as a plasminogen receptor to promote cell migration and cancer metastasis 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 14 No specific inhibitor of ENO1 has been found that regulates the activity of enolase. 15 However, few studies have investigated the relationship between ENO1 and tumors, and of those that exist, the research results are inconsistent. Zhang et al 14 detected the protein expression of ENO1 in tissues and serum samples obtained from 42 healthy participants, 34 patients with benign lung lesions, and 84 patients with non-small cell lung cancer (NSCLC); this study found that the protein the expression of ENO1 in NSCLC tissues was significantly higher than in corresponding normal lung tissue ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…ENO1, one of four types of Enolase isozymes, has been detected in almost all mature tissues [22,23]. The functions of ENO1 is now considered to be both a plasminogen receptor, which can promote in ammatory responses in several tumors [24], and a glycolytic enzyme, which participates in catalyzing the penultimate step in glycolysis [23]. As a glycolysis enzyme, ENO1 can be overexpressed and activated by several glucose transporters and glycolytic enzymes that participate in the Warburg effect in cancer cells [25].…”
Section: Read Full Licensementioning
confidence: 99%